Construct Validity of the OMNI Resistance Exercise Scale - Lagally, Kristen M.; Robertson, Robert J. (Journal of strength and conditioning research, 2006)
This study examined the construct validity of the Adult OMNI Perceived Exertion Scale for Resistance Exercise (OMNI-RES). Forty (20 men and 20 women) subjects performed 1 repetition of the knee extension exercise at 40, 50, 60, 70, 80, and 90% of the 1 repetition maximum. Active muscle and overall body ratings of perceived exertion (RPE) were collected from the Borg 15-category RPE scale and the OMNI-RES immediately following each repetition. Construct validity was established by correlating RPE from the OMNI-RES with RPE from the Borg RPE scale using regression analysis. The results indicated a positive and linear relationship between RPE from the OMNI-RES and RPE from the Borg scale for both men and women. Validity coefficients ranged from r = 0.94 to 0.97. The high level of construct validity indicates that the OMNI-RES measures the same properties of exertion as the Borg RPE scale during resistance exercise and suggests that the 2 scales can be used interchangeably during resistance exercise.